2021
DOI: 10.3390/brainsci11050616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Vocalizations Emission across Development in Rats: Coordination with Respiration and Impact on Brain Neural Dynamics

Abstract: Rats communicate using ultrasonic vocalizations (USV) throughout their life when confronted with emotionally stimulating situations, either negative or positive. The context of USV emission and the psychoacoustic characteristics of the vocalizations change greatly between infancy and adulthood. Importantly, the production of USV is tightly coordinated with respiration, and respiratory rhythm is known to influence brain activity and cognitive functions. This review goes through the acoustic characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 167 publications
(220 reference statements)
0
7
0
Order By: Relevance
“…Importantly, nearly all of the USV playback research has been performed on male recipient rats with male rat stimulus vocalizations, despite the evidence that male and female rats respond differently to alarm calls, and their own vocalizations have different qualities and tendencies of emission (Boulanger-Bertolus and Mouly, 2021 ; Lenell et al, 2021 ). One study found reduced locomotion in male and female rats exposed to alarm calls, but females retained this behavioral inhibition even after the stimulus ended (Wöhr et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, nearly all of the USV playback research has been performed on male recipient rats with male rat stimulus vocalizations, despite the evidence that male and female rats respond differently to alarm calls, and their own vocalizations have different qualities and tendencies of emission (Boulanger-Bertolus and Mouly, 2021 ; Lenell et al, 2021 ). One study found reduced locomotion in male and female rats exposed to alarm calls, but females retained this behavioral inhibition even after the stimulus ended (Wöhr et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A potential function of vibrissae in the dispersion of pheromones has been suggested early on (Marler and Hamilton, 1966 ; Ahl, 1986 ) but never investigated in fine detail. The fact that whisking and sniffing are strongly correlated and operate at the same frequency (4–12 Hz; Welker, 1964 ; Ranade et al, 2013 ) supports a synergistic action of touch and smell together with audition, as USVs have been shown to be emitted during active sniffing periods (Roberts, 1972 ; Riede et al, 2011 ; Sirotin et al, 2014 ), locked to exhalation (Riede, 2014 ; Boulanger-Bertolus and Mouly, 2021 ). As already mentioned, a possible synergistic interaction between touch and smell becomes even more apparent after the initial approach takes place: male and female mice, and rats, not only closely investigate each other’s faces but also sniff and whisk all over their bodies and most importantly their anogenital region (Lenschow and Lima, 2020 ).…”
Section: The Impact Of Somatosensation For Rat and Mouse Mate Choice ...mentioning
confidence: 97%
“…Calls from rat pups can be categorized into a lower frequency class with a peak around 30–40 kHz, and a higher frequency class at 50–66 kHz 82,93,94 . In rodent infants both frequency call classes have negative valence, 95 in contrast to juvenile and adult rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Age‐dependent changes in USV emission are tightly linked to maturation of laryngeal function and innervation, the development of ultrasound representation in the auditory cortex, and to the brain circuitries that regulate respiration and arousal—processes that are associated with developmental milestones that can be dysfunctional in ASD 93,95,117–119 . The usage of simple, frequency unmodulated calls typically decreases during development, 40 whereas the usage of frequency modulated calls increases 40,120 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation